Penegakan Hak Buruh oleh Konfederasi Serikat Pekerja Maros; Eksistensi dan Peranan - Hisbullah, Hisbullah; Sofyan,; Mulham Jaki Asti,; Kurniati,; Misbahuddin, (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
Violation of workers' rights in Indonesia is a central issue in labor relations Commonly violations of workers' rights demand the existence of the Confederation of Trade Unions as an organization formed from, by, and for workers both in the company and outside the company, which is free, open, independent, democratic, and responsible to fight for, defend and protect the rights and interests and welfare of workers. For this reason, this research is oriented in the form of normative empirical research that seeks to observe the provisions of laws and regulations from the aspects of the rights and obligations of workers and employers along with law enforcement and direct observations in the Confederation of Maros Trade Unions in their role defending the rights and interests of workers in Maros Regency. The conclusion in this study is that labor relations outline the existence of inseparable rights and obligations as a definite causality, so disputes over rights and obligations between workers and employers require law enforcement that can be pursued outside the court through Bipartite settlements and mediation and litigation settlements through judicial institutions. In addition, the existence of KSPI Maros plays a very important role in industrial relations and efforts to resolve labor rights disputes through Bipartite, mediation and courts.